Teologi Advokasi Terhadap Kerusakan Lingkungan Alam Sabuai - Advensia Kakisina; John Chr Ruhulessin; Eklefina Pattinama (Program Pascasarjana UKIM, 2023)
The purpose of the research is to analyze the causes and impacts of environmental problems that arise as a result of the operation of the Commanditaire Vennootschap (CV). Sumber Berkat Makmur in the Sabuai area and examines the advocacy role of the church and government. Through field research, it was found that environmental problems arose due to a lack of government oversight as the permit provider for CV. Source of Prosperous Blessings. There was an abuse of power in the process of companies entering to operate in the Sabuai customary forest in relation to social promises to the community. Environmental damage is also related to socio-cultural problems in society, increasing poverty, social injustice, and natural destruction. Communities as victims continue to struggle by carrying out protest actions, such as sasi adat, the ritual of protecting the forests, destructing company facilities, and demonstrating against the government. In this case, advocacy theology's role is not limited to spreading news from church pulpits, more than that, fighting with the people to get justice and advocating for environmental damage issues.